Sesquioxide properties, charge characteristics and mineralogical properties of soils under different land uses in Universiti Putra Malaysia, Selangor - Abdul Malik, Mohammad Nazrin; Abdu, Arifin; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Karim, Md. Rezaul; Abdul Hamid, Hazandy; Jamaluddin, Aiza Shaliha; Rajoo, K. S.; Patek Mohd, Nur Nazirah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Malaysia has to strike a balance between development and conservation of tropical forest. Land use change encompasses the ways in which human use of land has varied through time. Kumar (1986) reported that changes in land use pattern under forest cover are due to agricultural activities such as rubber, oil palm and cocoa plantation and non-forested land from 1960 to 2005. In this study, soil profiles were dug and samples were collected according to genetic horizons to assess the impact of land use/land cover of five land use types, namely Pinus caribaea plantation (PP), Swietennia macrophylla plantation (MP), pasture area (PA), oil palm plantation (OP) and secondary forest (SF), Universiti Putra Malaysia Serdang Selangor, Malaysia.The clay mineral composition was dominated by 1:1 type kaolin minerals. The point zero of salt effect values tended to increase, while the σp values decreased with depth at all sites, indicating that the soils were highly weathered. Therefore, it could be concluded that results from these sites were influenced by the weathering of the parent materials, human activities, and vegetation and it is required to employing integrated soil fertility management in sustainable manner to optimize and maintain the favorable soil physicochemical properties.